Performance test on triple heap sort algorithm - Marszałek, Zbigniew (Technical Sciences, 2017)
Rapid information search in large data sets is one of the most important issues. Quite often it leads sorting strings stored in different cultures, languages. In this work the author presents a modified triple heap algorithm to sort strings for large data sets. Triple heap algorithm is the subject of research and demonstrating its usefulness in applications.